Task Masking Among Generation Z Employees: A Conceptual Framework For Understanding Performative Productivity In Contemporary Workplaces - Supriadi, Supriadi (Journal of Management, Economic, and Accounting, 2024)
This conceptual paper introduces and theoretically examines the emerging phenomenon of task masking among Generation Z employees. Task masking refers to performative productivity behaviors, where young workers appear busy and productive while actually concealing a lack of meaningful output. This study develops a comprehensive theoretical framework to understand how such behaviors emerge as responses to organizational control mechanisms, such as return-to-office (RTO) mandates and presence-based evaluations. By synthesizing insights from workplace observations, media reports, and preliminary organizational studies, the paper conceptualizes task masking as a three-dimensional construct: performative visibility, productivity simulation, and output avoidance. The proposed theoretical model links organizational antecedents—including micromanagement and attendance-based assessment—to task masking behaviors and their consequences at both individual and organizational levels. Five theoretical propositions are offered for future empirical testing. In terms of practical implications, organizations are encouraged to reassess productivity measurement systems that reward appearances over actual contributions. Management practices should align with contemporary workforce expectations, emphasizing autonomy and outcome-based evaluation. This paper contributes original value by introducing task masking as a novel theoretical construct in organizational behavior literature. It offers the first systematic conceptual framework to understand this growing phenomenon among Generation Z employees, calling for further empirical validation across diverse work settings.